Turning Points in the U.S. Civil War: A British Perspective - William O. Brown Jr.; Richard C.K. Burdekin (Claremont McKenna College, Department of Economics, 1999)
This paper examines the Confederate cotton bonds floated in Europe in March 1863 and traded on the London market. Over our March 27, 1863 to June 17, 1865 sample we isolate two, non-reversed, 'turning points' that follow news of Confederate defeat at Gettysburg and Vicksburg in July 1863 and the fall of Atlanta in September 1864. Our analysis suggests that the turning points important to Southern interests differ from those identified for the Northern side by Willard, Guinnane and Rosen (1996). It seems that war news did not always have symmetric effects on North and South.
Keywords: 330